Implementasi Algoritma Noekeon Untuk Mengamankan File Audio - Tita Azwinar Sarumaha (Journal of Informatics Management and Information Technology, 2022)
Along with the development of an increasingly advanced era, and supported by the development of very rapid information technology, especially in producing audio files, it can now be done with smartphone devices. With the application on smartphones with devices to make audio both for private and public. Audio files need to be secured with better security, in order to anticipate if the account is far from being in the hands of unauthorized people, one way to secure audio files is by using cryptographic techniques, with this technique, unauthorized people cannot see the information contained in the audio. the. One of the algorithms that can be used to secure audio files is the NOEKEON algorithm, Noekeon is a repeating block cipher with a block length and key length of 128 bits each, which consists of a simple round transformation application that repeats itself, followed by an output transformation. Noekeon has 16 rounds (Nr) iterations in each round four transformations are carried out, namely, Theta, shift offset consisting of two transformations Pi1 and Pi2 and gamma The advantages of the Noekeon algorithm do not limit the keys used or use these keys to exploit into cipher text and avalanche effects obtained meet the strict Avalanche criterion. If there is an error in one block cipher it cannot affect the other blocks